UJI TOKSISITAS AKUT EKSTRAK ETANOL DAUN MALAKA (Phyllantus emblica) TERHADAP MENCIT (Mus musculus). (Acute Toxicity Test of Ethanolic Extract of Malaka (Phyllantus emblica) Leaves on Mice (Mus musculus)) - T. Armansyah TR; Sudi Indriany; Amalia Sutriana; Rosmaidar Rosmaidar; Nuzul Asmilia; Budianto Panjaitan; Dwinna Aliza; Hamdan Hamdan (Universitas Syiah Kuala, 2016)
ABSTRACT The aim of this research was to asses the acute toxicity of ethanolic extract of malaka leaves using lethal dose 50 (LD50) on mice (Mus musculus). Twenty male mice weighing between 20-30 g were randomly divided into 4 groups (group K1-K4) of 5 mice each. All mice in group K1, K2, K3, and K4 were administered ethanolic extract of malaka leaves with the dose of 2, 4, 8, and 16 g/kg bw, respectively. Single dose of ethanolic extract of malaka leaves were given by oral gavage prior to clinical observation . The observation period was 14 days post administration, for sign of toxicity symptom, weight loss, and mortality. The result showed that no mortality was observed in the experimental animals during this study. Slight reduction of body weight was observed in group K2, K3, and K4, and no toxicity sign was found during fourteen days of observation. The LD50 of ethanolic extract of malaka leaves was higher than 16 g/kg body weight, thus, the substance was practically non toxic substance.